2020
DOI: 10.3390/w12092398
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Framework for Stakeholder Engagement Using the Basin Futures Platform

Abstract: Water resources are under growing pressures globally, and better basin planning is crucial to alleviate current and future water scarcity issues. Communicating the complex interconnections and needs of natural and human systems is a significant research challenge. With advances in cyberinfrastructure allowing for new innovative approaches to basin planning, this same technology can also facilitate better stakeholder engagement. The potential benefits of using digital basin planning platforms for stakeholder en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…One very good example in a recent study demonstrated the use of a digital platform, Basin Futures, for stakeholder engagement [100], which is worth looking into for the effective implementation of a stakeholder engagement framework.…”
Section: The Need For a Multi-stakeholder Platformmentioning
confidence: 99%
“…One very good example in a recent study demonstrated the use of a digital platform, Basin Futures, for stakeholder engagement [100], which is worth looking into for the effective implementation of a stakeholder engagement framework.…”
Section: The Need For a Multi-stakeholder Platformmentioning
confidence: 99%
“…Sangle (2010) showed that effectively engaging stakeholder groups is a critical success factor in public sector CSR in India. Yet, despite the impressive performance of the public sector in CSR in India, one major concern has been ineffective stakeholder engagements (O'Sullivan et al, 2020). Ray (2013), in this regard, pointed out that for CSR to be more effective public sector stakeholder engagements needed to be streamlined.…”
Section: Public Sector and Csrmentioning
confidence: 99%
“…By engaging with stakeholders, organizations can achieve their CSR objectives and ensure that their decisions and activities are socially acceptable (Green & Hunton-Clarke, 2003). However, (O'Sullivan et al 2020) pointed out that stakeholder engagement is often undertaken in an ad-hoc and ineffective manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collaborative modelling approach spanned central and multiple basin state governments, as well as NGOs and development partners. O'Sullivan et al [8] focus specifically on the challenges of stakeholder engagement in large river basins. They present a new integrative framework for stakeholder engagement built around a cloud-based web application for basin modelling and planning that relies heavily on open access Earth observation datasets.…”
mentioning
confidence: 99%